Ore crushing process dynamics modeling using the laguerre model - Михайленко, Олексій Юрійович (Eastern-European Journal of Enterprise Technologies, 2015)
The problem of ore crushing process dynamics modeling using the orthonormal Laguerre functions was considered. The analysis has shown that the maximum sampling interval that will allow to reconstruct the transition process by the discrete sample is 1.3 seconds. As expected, the structure that includes only the first-order Laguerre filter has the worst accuracy. Increasing the number of functions in the orthonormal system leads to the higher modeling quality of the crushing process output. It was also determined that the relationship between the scale factor and mean square error of identification is unimodal in nature, therefore, it is advisable to use optimization methods for finding the optimal value for this parameter. The research has allowed to reveal the structure and the scale factor of the Laguerre model, and the sampling interval, which allow to ensure the minimum mean square error when using the least squares method for estimating the model parameters.